Digital Competency Gap and Organizational Readiness in E-Government Implementation across Indonesia's 3T Regions - Suhelmi Helia; Asnil Asnil; Ronal Regen; Wazirman Wazirman (Fundamental and Applied Management Journal, 2026)
The implementation of e-government in Indonesia's disadvantaged, frontier, and outermost (3T) regions still faces various challenges related to the digital competence of civil servants, human resource management support, and organizational readiness. Previous research has focused more on technological and infrastructure aspects, while the integrated role of human resource capacity and organizational readiness in supporting e-government implementation is still limited. Based on the Resource-Based View (RBV), Technology Acceptance Model (TAM), and Organizational Readiness perspective, this study aims to analyze the influence of Digital Competency and Human Resource Management Support on E-Government Implementation through Organizational Readiness. The study uses a quantitative explanatory approach involving 200 government officials in the disadvantaged, frontier, and outermost (3T) regions of Indonesia. Data analysis was conducted using Structural Equation Modeling–Partial Least Squares (SEM-PLS). The results show that Digital Competency and Human Resource Management Support have a positive and significant effect on Organizational Readiness and E-Government Implementation. Organizational Readiness also positively influences E-Government Implementation and partially mediates the relationship between Digital Competency and Human Resource Management Support with E-Government Implementation. The research model has moderate explanatory power, with R2 values of 0.392 for Organizational Readiness and 0.521 for E-Government Implementation. This finding emphasizes the importance of strengthening organizational readiness as a key mechanism to optimize sustainable digital transformation in local governments within the disadvantaged, frontier, and outermost (3T) regions.